2022
DOI: 10.1186/s12903-022-02389-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and characteristics of CAD/CAM zirconia and glass ceramics after combined treatment procedures

Abstract: Background The roughening of the inner surface of a fixed ceramic restoration is an important factor for the bonding process. The aim of this study is to investigate the effect of combined surface treatments (acid etching, air-abrasion and Er: YAG Laser) on surface roughness of CAD/CAM fabricated zirconia (ZrO2) and lithium-disilicate glass ceramics (LDS). Methods Sixty ZrO2 (Ceramill Zi) and LDS (IPS e.max CAD) specimens, (5 mm in width, 5 mm in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Zirconia changes phases disruptively when heated. After cooling from high temperatures, the structure cracks due to significant strains induced by the volume shift brought on by the structure’s transition from tetragonal to monoclinic to cubic [ 46 , 47 ]. It has also been reported as utilizing a finishing and polishing procedure instead of glazing to create a more natural texture because glazing typically wears off over time [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zirconia changes phases disruptively when heated. After cooling from high temperatures, the structure cracks due to significant strains induced by the volume shift brought on by the structure’s transition from tetragonal to monoclinic to cubic [ 46 , 47 ]. It has also been reported as utilizing a finishing and polishing procedure instead of glazing to create a more natural texture because glazing typically wears off over time [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to realize that a material's hardness does not always indicate that it would cause greater abrasion on the opposing tooth's enamel surface [80]. Conversely, a number of tests revealed that in contrast to glass ceramics with a greater degree of surface roughness, translucent monolithic Zr has less wear effect on the opposing enamel because of its smooth polished surface [81]. The antagonist's natural dentition becomes more abrasive and has a rougher surface when the glass-ceramics microstructure disappears and reveals the crystalline phase.…”
Section: Effect On Antagonist Teethmentioning
confidence: 99%